PROPHET KHIDIR IN KUNTOWIJOYO’S NOVEL WASRIPIN DAN SATINAH: WOLFGANG ISER’S AESTHETIC RESPONSE ANALYSIS - Inung Setyami; Faruk Faruk; Fadlil Munawwar Manshur (Jurnal Poetika, 2022)
This study aims to describe and reveal the meaning of the figure of the Prophet Khidir as a repertoire in Kuntowijoyo's Wasripin dan Satinah novel in terms of Wolfgang Iser's Aesthetic Response theory. This study is qualitative descriptive, and the data source is the novel Wasripin dan Satinah published by Kompas Publisher in 2003. Using a note-taking technique of all novels related to the Prophet Khidir’s repertoire, it obtained the data. The technique was through 1) identification, 2) classification, 3) interpretation, and 4) inference. The results showed that 1) the figure of the Prophet Khidir in the novel Wasripin dan Satinah was an earlier reference in the text used by Kuntowijoyo as the basis or background for creating his novel. The transformed story of the Prophet Khidir in the Al-Qur'an has a different storyline. 1) In the Al-Qur'an, Prophet Khidir was approached by Prophet Musa to learn. Meanwhile, in the novel Wasripin and Satinah, the Prophet Khidir came to Wasripin to give his knowledge. 2) The novel Wasripin dan Satinah which represents the figure of Prophet Khidir, has given rise to myths in the lives of Javanese people. 3)  an intention conveyed by Kuntowijoyo in presenting the figure of the Prophet Khidir in his work, namely a lesson not to be shirk by glorifying or deifying someone who has superior abilities.